2010
DOI: 10.1016/j.apsoil.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Responses of bacterial and archaeal ammonia oxidizers to soil organic and fertilizer amendments under long-term management

Abstract: 17Ammonia oxidizing bacteria (AOB) and ammonia oxidizing archaea (AOA) co-exist in soil, 18 but their relative distribution may vary depending on the environmental conditions. Effects of 19 changes in soil organic matter and nutrient content on the AOB and AOA are poorly 20 understood. Our aim was to compare effects of long-term soil organic matter depletion and 21 amendments with labile (straw) and more recalcitrant (peat) organic matter, with and without 22 easily plant-available nitrogen, on the activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
119
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 37 publications
17
119
4
Order By: Relevance
“…2A) and nitrifiers' abundance (especially AOA) (Fig. 2C) although AOA and AOB were considered as autotrophy, which was agreed with the previous study that degradable straw could stimulate the soil nitrification activity (Wessen et al, 2010). Contrary to denitrification, aquatic plant detritus was more effective to nitrification indicated by the higher PNR and higher amoA gene abundance than terrestrial plant detritus.…”
Section: N Removal Performance and Mechanismssupporting
confidence: 77%
“…2A) and nitrifiers' abundance (especially AOA) (Fig. 2C) although AOA and AOB were considered as autotrophy, which was agreed with the previous study that degradable straw could stimulate the soil nitrification activity (Wessen et al, 2010). Contrary to denitrification, aquatic plant detritus was more effective to nitrification indicated by the higher PNR and higher amoA gene abundance than terrestrial plant detritus.…”
Section: N Removal Performance and Mechanismssupporting
confidence: 77%
“…The negative correlation between AOA and clay content could be indicative of AOA being less abundant in nutrient-rich environments, as clay soils have higher cation exchange capacity and bind more ammonium. Soil pH as a differentiating factor for the AOB and AOA habitats have been discussed previously, but there are conflicting results, with some studies showing a negative correlation to pH, as in our study , and others showing that the AOA are negatively impacted by low pH (He et al, 2007;Hallin et al, 2009;Jia and Conrad, 2009;Bru et al, 2010;Wessén et al, 2010). Contradictory results concerning the effect of pH on AOA abundance could be explained by differences in the physiological diversity within the archaeal communities present in different soils.…”
Section: Discussioncontrasting
confidence: 45%
“…Although it is well documented that the ratio of AOA:AOB ranges widely in soils (Leininger et al, 2006;He et al, 2007;Adair and Schwartz, 2008;Shen et al, 2008;Schauss et al, 2009;Di et al, 2010;Wessen et al, 2010;Zeglin et al, 2011), no data exist on what might influence this ratio, or its dynamism. Our study showed that the AOA:AOB shifts were generated by a combination of different phenomena: These observations raise some interesting questions about the environmental drivers of AOA and AOB growth, as well as about their relative stress tolerances.…”
Section: Discussionmentioning
confidence: 99%
“…A case can be made that the relative contributions of AOA and AOB to soil nitrification might shift in different phases of crop rotation and during different seasons of the year. Although recent studies have evaluated AOA and AOB population sizes, composition and/or their relative growth responses in soils recovered from agricultural cropping systems, the soils were often taken from complex crop rotations in multi-year cycles, and sampled in either spring, fall or unspecified times (Tourna et al, 2008;Hallin et al, 2009;Wessen et al, 2010Wessen et al, , 2011Xia et al, 2011). Clearly, the extent to which phase of the crop rotation or time of soil sampling might have influenced the results cannot be determined.…”
Section: Introductionmentioning
confidence: 99%